THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, COMPETENCE, AND SELF-EFFICACY ON ORGANIZATIONAL COMMITMENTS, AMBIDEXTERITY ORGANIZATIONAL AND PERFORMANCE OF VILLAGE GOVERNMENTS IN EAST NUSA TENGGARA PROVINCE - darmawa, wayan (Archives of Business Research, 2019)
This study aims to prove and analyze the influence of transformational leadership, organizational culture, competence, and self-efficacy on organizational commitment, organizational ambidexity and performance of village governments in East Nusa Tenggara Province. The population in this study were village heads in 21 regencies in East Nusa Tenggara Province which numbered 2,952. The samples in this study were 353 village heads. The data used in this study are primary data sourced from the questionnaire. Data analysis and hypothesis testing in this study using the Structural Equation Model (SEM). The results showed that the transformational leadership variables had a positive but not significant effect on performance, organizational commitment, organizational ambide on village government in East Nusa Tenggara Province. Organizational culture has a negative but not significant effect on performance. Organizational culture has a positive but not significant effect on organizational commitment, culture has a positive and significant effect on the organizational ambidexity of village governments in East Nusa Tenggara Province. Competence has a positive and significant effect on performance. Competence has a positive but not significant effect on organizational commitment, organizational ambide on village government in East Nusa Tenggara Province. Self-efficacy has a positive but not significant effect on performance, self-efficacy has a positive and significant effect on organizational commitment, organizational ambide in village government in East Nusa Tenggara Province. Organizational commitment has a positive but not significant effect on the performance, organizational ambide of village government in East Nusa Tenggara Province. The ambition of organizational organizational has a positive and significant effect on the performance of village governments in East Nusa Tenggara Province.